Hydrothermal synthesis of CuO/rGO nanosheets for enhanced gas sensing properties of ethanol. Issue 4 (15th February 2023) - Meng, Fanli; Yang, Zhiqiang; Yuan, Zhenyu; Zhang, Haoting; Zhu, Hongmin
Abstract: In this work, CuO nanosheets and CuO/rGO nanocomposites are synthesized by one-step hydrothermal method and characterized accordingly. Next, these samples are tested for gas sensing performance. The test data show that the CuO/rGO sensors have significantly improved gas sensing performance for ethanol compared to the pure CuO sensor. It should be noted that the CuO/rGO-10 sensor has the most outstanding gas sensing performance among the four sensors prepared, with an optimum working temperature 25 lower than that before doping, and its response value for 100 ppm ethanol at 175 °C is 10.54, which is 3.75 times higher than that before rGO doping. Also, the CuO/rGO-10 sensor has remarkable selectivity and reproducibility for ethanol. Most importantly, its limit of detection for ethanol is 100 ppb. At last, the gas sensing mechanism of the composites for ethanol is explained. Enhanced gas sensing performance of CuO/rGO sensors for ethanol is attributed to the lamellar structure and the synergistic effect between CuO and rGO.